MODEL DINAMIKA CINTA DENGAN MEMPERHATIKAN DAYA TARIK PASANGAN - Suci Rahma Nura; Mahdhivan Syafwan (Jurnal Matematika UNAND, 2014)
This article discusses a model of a love affair between two individuals by takinginto account the effect of the appeal of each individual. There are three important thingsthat must be considered in this model ; i.e, oblivion (the forgetting process), return (thepleasure of being loved), and instict (reaction to the partner’s appeal). Some dynamicalproperties of the model and its interpretations are also elaborated in this article.